Three new species and one new record of Tullbergiidae (Collembola: Onychiuroidea) from Tierra del Fuego - Arbea, Javier I. (Zootaxa, 2016)
Three new species, Tullbergia rapoporti sp. nov., Dinaphorura nerudai sp. nov. and Dinaphorura najtae sp. nov., and one new record, Tullbergia meridionalis Cassagnau & Rapoport, 1962 are described based on specimens from Tierra del Fuego. Tullbergia rapoporti sp. nov. is similar to T. crozetensis, but can be distinguished from it by the presence of an empodial appendage and the chaetotaxy of Abd VI. Dinaphorura nerudai sp. nov. is diagnosed by the dorsal pso formula, the seven spiniform processes on Abd VI, an elongate PAO, the absence of vesicle on Ant IV and the dorsal chaetotaxy. Dinaphorura najtae sp. nov. is characterised by the dorsal pso formula, the seven spiniform processes on Abd VI, a triangular PAO, the absence of vesicle on Ant IV and the dorsal chaetotaxy.